2012
DOI: 10.2174/138161212802083707
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Link Mechanisms between Inflammation and Cancer

Abstract: Inflammation is part of the body's response to internal and external environmental stimuli that normally eliminate the aggressor agent and restore the tissue physiology. However, when it becomes chronic, it can cause several pathologies such as cardiovascular, diabetes, rheumatoid arthritis, Alzheimer's autoimmune diseases and cancer. Currently, epidemiological data indicate that over 25% of all cancers are related to chronic infections and other types of unresolved inflammation. Further evidence of this relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
268
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(284 citation statements)
references
References 153 publications
1
268
0
15
Order By: Relevance
“…Nowadays, different studies have shown the involvement of the inflammatory process in the development and progression of several cancer types, including PCa (De Marzo et al 1999, Hamid et al 2011, Vendramini-Costa & Carvalho 2012, Thapa & Ghosh 2015. It is known that the etiology of prostatic inflammation is multifactorial, involving infectious agents, factors related to aging, eating habits among others (De Marzo et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, different studies have shown the involvement of the inflammatory process in the development and progression of several cancer types, including PCa (De Marzo et al 1999, Hamid et al 2011, Vendramini-Costa & Carvalho 2012, Thapa & Ghosh 2015. It is known that the etiology of prostatic inflammation is multifactorial, involving infectious agents, factors related to aging, eating habits among others (De Marzo et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation characterised by elevated levels of pro-inflammatory cytokines leads to activation of inducible nitric oxide synthase (iNOS) and increased activity of several transcription factors, such as NF-κB (nuclear factor κB), AP-1 (activator protein 1) and STAT3 (signal transducer and activator of transcription 3) leading in turn to upregulated activity of NADPH oxidase (NOX) and mitochondrial oxidoreductases 91 . The activation of these enzymes and transcription factors lead to the chronic activation of a wide range of inflammatory pathways subsequent to the up-regulation of COX-2 (cyclo-oxygenase-2), and the development of a state of chronic O&NS characterised by excessive production of reactive oxygen species (ROS), such as the superoxide anion, and reactive nitrogen species (RNS), such as nitric oxide (NO), which are known to play a major role in the pathogenesis and pathophysiology of major depression and inflammatory cancers 92 .…”
Section: Effects Of Oxidative and Nitrosative Stress (Oandns)mentioning
confidence: 99%
“…Flurbiprofen axetil is a new type of non-selective COX inhibitors, which has been widely used for preemptive analgesia (Sánchez et al, 2012), the prevention of propofol injection pain (Mizushima et al, 1986;Park et al, 1999), and the reduction of postoperative pain (Xu et al, 2008;Vendramini-Costa et al, 2012) and cancer pain (Davies et al, 1995;Hao et al, 2013), including metastatic bone pain and multiple breakthrough pain. Wu et al reported that intravenous flurbiprofen axetil can provide better analgesic effect and few side effects for the patients with refractory cancer pain (Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%